The Eastern Mediterranean security architecture, and the relations between Israel and Cyprus in terms of global power relations - Canyaş, Huseyin; Kocakuşak, Suha; Canyaş, F. Orkunt (My University, 2013)
The Island of Cyprus has hitherto maintained its importance on the global political agenda ever since different historical periods. This importance has been further increasing in the context of the Eastern Mediterranean, Middle East, and North Africa countries that are in the process of re-structuring. The Island of Cyprus is important also because it is close to the transportation terminals in the Eastern Mediterranean, which provides an outlet for the energy sources in the region, and it is so located as to keep these sources under control. Cyprus has gained importance in terms of global security balance that has changed in the 21st century. However, apart from the global positioning, the most important concept in Turkish national security policy in terms of external security is Close Environmental Safety, Strategic Perception and its understanding. In this regard, Cyprus has become an indispensable isle for the Security Architecture established in the Eastern Mediterranean Cyrus that can be defined as Core Security Region is important not only for her political stakeholders England, Turkey and Greece but also for Israel. Jewish culture having the conception of super ethnic origins makes it necessary for Israel to influence not only the land on which it was founded, but also the Eastern Mediterranean. We can say that Cyprus is a gate opening to the West for Israel.
Dogu Akdeniz Guvenlik Mimarisi ve Kuresel Guç Ilişkileri Bakimindan Israil, Kibris Ilişkileri
Keywords: Cyprus; Eastern mediterranean; Global politics; Israel; The middle east